Design and Validation of a JotForm-Based Arabic Language Assessment Model to Enhance Higher-Order Thinking Skills in Islamic Senior High Schools - Anawiyah Anawiyah; Lailatul Qomariyah (Institut Agama Islam Negeri Curup, 2026)
Students' critical thinking skills in Arabic language learning at Madrasah Aliyah are still relatively low, as evidenced by researchers' observations, which show that students are still at the stage of understanding and applying the material they are learning. This is due to the assessment method still being the old method, namely paper-based evaluation. This research aimed to develop a JotForm-based evaluation tool and test its validity. This research uses the Research and Development method with the ADDIE research model: 1) Analysis, 2) Design, 3) Develop, 4) Implement, and 5) Evaluation, and the researcher only focuses on the ADD stage, namely 1) Analysis, 2) Design, and 3) Develop. In the analysis stage, the researcher went through three steps: needs analysis, curriculum analysis, and materials analysis. In the design stage, the researcher developed the evaluation tool product. The development stage then refined the design into an Arabic-language learning evaluation tool using the JotForm application. This Jotform tool was designed to improve and develop students' critical thinking skills. Based on the calculation, the material validation results obtained a score of 75%, which falls within the range of 62.5%≥ - 81.5%, and can be classified as “valid and appropriate” for use and tested without review. At the same time, the media verifier results scored 87%, which falls within the range of ≥ 81.5% - 100% and is classified as very valid and can be used with the reviews provided. The language verifier scored 81%, which falls within the range of ≥ 62.5% - 81.5% and is classified as valid. Thus, Jotform is highly valid and well-suited as an evaluation tool that supports students' critical thinking skills.